Environmental drivers of seed persistence and seedling trait variation in two Neltuma species (Fabaceae) - Renzi Pugni, Juan Pablo; Quintana, Matias; Bruna, Matias Nicolas; Reinoso, Omar Juan (Cambridge University Press, 2025)
The endemic tree Neltuma caldenia Burk. and the shrub Neltuma flexuosa var depressa F.A. Roig (Fabaceae; subfam: Mimosoideae) are two promising species from the central region of Argentina, with high potential for use in the restoration of disturbed environments, for extensive livestock grazing and apiculture. Both species have seeds with physical dormancy. Ecological study of native species is important from the point of view of rehabilitation of degraded areas by natural regeneration or via seed-based programmes. The objective of this study was to evaluate soil seed bank persistence and seedling traits to understand variation among different populations of each of the study species growing along an ecological gradient and to identify potential components driving this variation. Home environments influenced seed bank persistence, which was higher in populations originating from more arid and unpredictable environments where it could act as a bet-hedging strategy between years and seasons. We also observed differences associated with seedling growth traits between the species and populations. Populations with higher seed persistence were associated with greater seedling growth in N. caldenia. The rapid elongation rate of N. caldenia seedlings growing in large populations and unstable environments could help their ability to escape drought by accessing deeper soil moisture and would confer a high relative competitive ability. In contrast, N. f. var depressa displayed higher seed persistence, which was associated with more arid and unstable conditions and correlated with lower seedling growth, possibly due to an inbreeding depression effect, resulting from the presence of mother plants in low-densities or being isolated from other individuals. There was no effect of population size on seed persistence. To better understand seed persistence and associated seedling trait variation, future studies need to consider the genotype, environment and landscape conditions.